The MedSafer Study: A Controlled Trial of an Electronic Decision Support Tool for Deprescribing in Acute Care - McDonald, Emily G.; Wu, Peter E.; Rashidi, Babak; Forster, Alan J.; Huang, Allen; Pilote, Louise; Papillon‐Ferland, Louise; Bonnici, André; Tamblyn, Robyn; Whitty, Rachel; Porter, Sandra; Battu, Kiran; et al. (Journal of the American Geriatrics Society (JAGS), 2019)
OBJECTIVES Polypharmacy is common, costly, and harmful for hospitalized older adults. Scalable strategies to reduce the burden of potentially inappropriate medications (PIMs) are needed. We sought to leverage medication reconciliation in hospitalized older adults by pairing with MedSafer, an electronic decision support tool for deprescribing. DESIGN This was a nonrandomized controlled before‐and‐after study. SETTING The study took place on four internal medicine clinical teaching units. PARTICIPANTS Subjects were aged 65 years and older, had an expected prognosis of 3 or more months, and were taking five or more usual home medications. INTERVENTION In the baseline phase, patients received usual care that was medication reconciliation. Patients in the intervention arm also had a “deprescribing opportunity report” generated by MedSafer and provided to their in‐hospital treating team. MEASUREMENTS The primary outcome was ascertained at the time of hospital discharge and was the proportion of patients who had one or more PIMs deprescribed. RESULTS A total of 1066 patients were enrolled, and deprescribing opportunities were present for 873 (82%; 418 during the control and 455 during the intervention phases, respectively). The proportion of patients with one or more PIMs deprescribed at discharge increased from 46.9% in the control period to 54.7% in the intervention period with an adjusted absolute risk difference of 8.3% (2.9%‐13.9%). Not all classes of drugs in the intervention arm were associated with an increase in deprescribing, and new PIM starts were equally common in both arms of the study. CONCLUSION Using an electronic decision support tool for deprescribing, we increased the proportion of patients with one or more PIMs deprescribed at hospital discharge as compared with usual care. Although this type of intervention may help address medication overload in hospitalized patients, it also underscores the importance of powering future trials for a reduction in adverse drug events. Trial registration: NCT02918058. J Am Geriatr Soc 67:1843–1850, 2019